Control of wall pressure flow field with micro jets and control effectiveness - Bashir, Musavir; Azam, Qummare; Khan, Sher Afghan; Baig, Maugal Ahmed Ali (IOSR journals, 2016)
This paper presents an experimental study of airflow from convergent-divergentnozzles discharged into enlarged duct, focusing attention on the flow development in the duct. To investigate the influence of active control on the flow field developed in the duct, the tiny jets of 0.05 mmradiuslocated at 900interval along the base at 6.5 mm from the main jet were employed. The Mach number tested in the present study was 1.48. The area ratio tested was 2.56. The NPR tested are from 3, 5, 7, and 9 respectively. The L/D ratio of the duct was varied from 10 to 1. The level of expansion at the nozzle exit influences the wall pressure very strongly. When the micro jets were activated they found to influence the base region, taking the wall pressure to considerably higher values, for most of the cases. Flow field in the duct with and without control remains the same.